Spillovers in the Nordic Countries - Mircheva, Borislava; Muir, Dirk. (Washington, D.C. : International Monetary Fund, 2015)
Denmark, Finland, Norway, and Sweden form a tightly integrated region which has strong ties with the euro area as well as some exposure to Russia. Using the IMF's Global Integrated Monetary and Fiscal model (GIMF), we examine spillovers the region could face, focusing on possible scenarios from the rest of the euro area and Russia, and the fall in global oil prices. We show that the spillovers from these scenarios differ in magnitude and impact, regardless of the high degree of integration among the four Nordic economies. These differences are driven by the fact that Denmark and Finland have no independent monetary policy, and Denmark and Norway are net energy exporters while Finland and Sweden are energy importers. We infer lessons for policy from the outcomes.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet